Pioneer herbaceous vegetation on glacier forelands from the Italian Alps - M.S. Caccianiga; C. Andreis (Phytocoenologia, 2004)
Abstract. The pioneer vegetation of the Holocene moraines of some Italian glaciers was studied by a phytosociological approach. Particular attention was given to mid-successional communities on stabilized terrains (19th century moraines). Sixty-seven releve ́s were performed on the forelands of 8 glaciers from the central and western Italian Alps, from continental inner alpine to oceanic prealpine areas. Early as well as late successional stages were sampled. Releve ́s were analyzed by cluster analysis using the Jaccard index and UPGMA as the clustering method. Two main clusters could be separated: 1) pioneer, low cover communities of recent and/or disturbed moraines; 2) high cover communities of already stabilized moraines, mainly ice-free since the 19th century. The first group included the pioneer community Sieversio-Oxyrietum digynae Friedel 1956, which can be divided into three subassociations: typicum, androsacetosum alpinae subass. nov. and a subtype with Epilobium fleischeri and Saxifraga aizoides. The second group includes species-rich coenoses occurring on stable but gravel terrains, ascribed to the Saxifrago bryoidis-Poetum alpinae ass. nov. (including subassociations trifolietosum pallescentis subass. nov. and salicetosum retusae subass. nov.), and continuous grasslands dominated by Poa alpina and Agrostis rupestris. The last type could be divided into a rankless Luzula alpinopilosa community and a Trifolium pallescens grassland (Agrostio rupestris-Trifolietum pallescentis ass. nov.). These plant communities are differentiated by many environmental factors. Terrain age and related parameters seem to play the main role: low-cover pioneer communities grow on 20th century deposits, whereas high-cover communities occur mainly on already stabilized moraines dating back to the 19th century. Altitude, aspect, insolation, morphology and parent material can also be determinant; altitude should be taken into account considering the local context of the altitudinal belts, which depends on the degree of ...